2018
DOI: 10.47672/aje.330
|View full text |Cite
|
Sign up to set email alerts
|

Real Interest Rate, Inflation, Exchange Rate, Competitiveness and Foreign Direct Investment in Kenya

Abstract: Purpose: The purpose of this study was to establish the effect of real interest rates, exchange rate, inflation and competitiveness on FDI in Kenya.  Methodology: The study used annual time series data for the period 1970-2016. The sources of data included World Bank Indicators and Kenya National Bureau of Statistics annual reports. Data was collected for the variables real interest rates, exchange rates, inflation rate, competitiveness/ease of doing business and FDI. The data for all the variables was in perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
2
3
0
4
Order By: Relevance
“…However, authors further suggested that the characteristics of countries indicated a substantial influence on the nature of the IR impact on FDI as well [25,26]. According to Musyoka [27] and Nyanyuki [28], both RIR and currency rates negatively and significantly influence FDI inflow in Kenya. In contrast, a study in Kenya highlighted that the IR has a favourable impact on FDI inflows to Kenya's energy and petroleum sector [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, authors further suggested that the characteristics of countries indicated a substantial influence on the nature of the IR impact on FDI as well [25,26]. According to Musyoka [27] and Nyanyuki [28], both RIR and currency rates negatively and significantly influence FDI inflow in Kenya. In contrast, a study in Kenya highlighted that the IR has a favourable impact on FDI inflows to Kenya's energy and petroleum sector [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, to increase more FDI into Pakistan, authorities of the country need to ensure a stable and low-interest rate level. By using annual time series data for the period 1970–2016, Musyoka and Ocharo [ 38 ] employed the OLS technique to determine the effect of real interest rate and exchange rate on FDI in Kenya. Empirical results show that real interest rates and exchange rates have a negative and significant influence on FDI inflows into Kenya.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hal ini didukung oleh teori marginal efficiency of capital yang menyatakan bahwa perusahaan internasional dalam berinvestasi akan memilih tingkat pengembalian yang tinggi dari tingkat bunganya. Penelitian ini sejalan dengan penelitian Kustina et al, (2018); Dewi & Triaryati, (2015); Sari & Baskara, (2018); Musyoka & Ocharo, (2018) dan Okafor, (2012) yang menyatakan bahwa suku bunga memiliki pengaruh pengaruh yang negatif dan signifikan tehadap Investasi Asing Langsung. Namun, tidak sejalan dengan penelitian Eliza & Ismail, (2012) ;Kiplagat, (2016); Septifany et al, (2015) dan Aditama et al (2014) yang menyatakan bahwa suku bunga berpengaruh positif dan signifikan terhadap investasi asing langsung.…”
Section: Pengaruh Suku Bunga Terhadap Investasi Asing Langsungunclassified
“…Hal ini didukung oleh teori the currency areas hypotesis yang menyatakan bahwa perusahaan asing yang memiliki nilai mata uang yang lebih kuat dibandingkan negara lainnya, cenderung akan berinvestasi dengan negara yang memiliki mata uang yang lebih lemah. Hasil penelitian ini sejalan dengan penelitian dari Musyoka & Ocharo, (2018);Kiplagat, (2016) dan Septifany et al, (2015), yang menyatakan bahwa Nilai Tukar memiliki pengaruh pengaruh yang negatif dan signifikan tehadap Investasi Asing Langsung. Namun, hasil penelitian ini tidak sejalan dengan penelitian Sari & Baskara, (2018); Akther & Shamima, (2016) dan Okafor, (2012) yang menyatakan bahwa nilai tukar berpengaruh positif dan signifikan terhadap investasi asing langsung.…”
Section: Pengaruh Nilai Tukar Terhadap Investasi Asing Langsungunclassified
See 1 more Smart Citation